Bilateral pheochromocytoma and medullary thyroid carcinoma in a middle-aged female: A case of Multiple endocrine neoplasia Type 2A - Akter, Nazia; Bhuiyan, Abdullah Al Noman; Hossain, Md. Saddam; Haq, Tahniyah; Fariduddin, Md. (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Multiple endocrine neoplasia type 2A (MEN 2A) is a rare autosomal dominant disorder characterized by the co-existence of medullary thyroid carcinoma (MTC), pheochromocytoma, and, less commonly, primary hyperparathyroidism. Here we present a case of a 43-year-old female who presented with recurrent hyperadrenergic spells along with sustained hypertension, bilateral loin pain, and unintentional weight loss for 1 year. Physical examination revealed thyromegaly and hyperpigmented patches in the interscapular region. Laboratory investigations showed elevated 24-hour urinary fractionated metanephrine, raised serum calcitonin and carcinoembryonic antigen, along with a normal serum calcium profile. A CT scan of the adrenal gland was suggestive of bilateral adrenal pheochromocytoma. Ultrasound of the thyroid gland demonstrated bilateral neoplastic nodules in both lobes of the thyroid gland. A provisional diagnosis of MEN 2A was made. Bilateral adrenalectomy was done, followed by total thyroidectomy with prophylactic central lymph node dissection. Her postoperative evolution was favourable. She is currently maintained on appropriate hormone replacement therapy. Genetic counseling was done, and family screening was advised. This case highlights the importance of early detection and timely surgical intervention in MEN 2A, which are pivotal for improving outcomes and enabling preventive family screening. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S55]